Probing the effect of the solution environment around redox-active moieties using rigid anthraquinone terminated molecular rulers - Darwish, Nadim; Eggers, P.; Ciampi, S.; Tong, Y.; Ye, S.; Paddon-Row, M.; Gooding, J. (American Chemical Society, 2012)
Herein, we report the influence of the position and the solution environment around surface-bound redox-active moieties on their redox reaction. The study was made possible by using rigid norbornylogous bridges, which possess anthraquinone (AQ) moieties. An L-shaped norbornylogous bridge (L-NB) and straight-shaped norbornylogous bridge (S-NB) were used to situate AQ moieties at well-defined position and environments above a mixed alkanethiol self-assembled monolayer (SAM) on Au (111) surfaces. Sum frequency generation (SFG) vibrational spectroscopy was employed to evaluate the interaction between the S-NB and L-NB with diluent molecules in the mixed SAMs. The SFG measurements demonstrated that hydrogen-bonding interactions were formed between AQ moieties of L-NB and diluent molecules terminated by hydroxyl group within a suitable separation. The SFG observations provided information about the relative position of the AQ moieties in each SAM, which significantly affects the thermodynamics and the kinetics of the electron transfer on the electrode/solution interface. The rate constant (k et) of the electron transfer between the AQ moiety and the gold surface and the apparent formal potential (E 0') were studied using cyclic voltammetry (CV), alternating current voltammetry (ACV), and electrochemical impedance spectroscopy (EIS). It was found that the k et increases and E 0' shifts to more anodic values as the distance between the AQ moiety and the surface of the diluent was increased, for both methyl and hydroxyl terminated diluent. These results are discussed in relation to H-bonding interactions with water surrounding the AQ moieties.